N, S co-doped hollow carbon sphere with Turing surface and preparation method thereof
By calcining PMMA@PPy and sulfur powder in an inert atmosphere, N,S co-doped hollow carbon balls with Turing surface were prepared, which solved the problems of few Turing structures and difficult preparation, and achieved efficient and low-cost Hollow carbon spheres of Turing structure have high specific surface area and rich interface.
Patent Information
- Application Number
- CN202411301570.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2024-12-27
AI Technical Summary
The prior art mainly relies on homogeneous or heterogeneous solution systems when building Turing structures, resulting in fewer structural types and difficult preparation, and most of them need to be carried out in high temperature and high pressure environments, which are costly and complex in operation.
Polymethyl methacrylate (PMMA) is used as a template, and polypyrrole (PPy) is coated on its surface, and calcined with sulfur powder at high temperature in an inert atmosphere to quickly decompose PMMA to prepare N,S co-doping with Turing surface Mixed hollow carbon balls.
In an inert atmosphere, a large-scale production of Turing structure hollow carbon spheres with uniform morphology was achieved, with significantly improved specific surface area and rich crystalline/amorphous interface, which reduced the preparation cost and simplified experimental operations.
Smart Images

Figure CN119191262A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of nano-carbon materials, and in particular relates to a N, S co-doped hollow carbon sphere with a Turing surface and a preparation method thereof. Background Art
[0002] Turing structures, also known as spatiotemporal steady-state structures, are usually produced in reaction-diffusion processes far from thermodynamic equilibrium. They are also widely found in nature, such as the veins of leaves and the ripples of deserts. Due to their unique static properties, Turing structures have important applications in biology, chemistry, and materials science. According to the "reaction-diffusion" model proposed by AMTuring, researchers have prepared a variety of Turing structures, in which the maze pattern composed of stripes has a highly curved feature, which gives the material a large specific surface area and rich crystalline / amorphous interfaces. These Turing structures have important application prospects in the fields of biology, materials, energy, and catalysis. However, the construction of Turing structures is currently mainly achieved in homogeneous or heterogeneous solution systems, resulting in a small number of Turing structures and difficulty in mass preparation. The present invention provides a preparation method that can be mass-produced in an inert atmosphere. Compared with traditional hollow carbon spheres, the specific surface area of carbon spheres with Turing surfaces is significantly improved, and they contain rich crystalline / amorphous interfaces, which can expand their application fields. Summary of the invention
[0003] The purpose of the present invention is to provide a method for preparing N, S co-doped hollow carbon spheres with Turing surfaces that can be prepared in an inert atmosphere, can be mass-produced, and have uniform morphology. The present invention first uses polymethyl methacrylate (PMMA) as a template, and coats polypyrrole (PPy) on its surface to obtain a polymethyl methacrylate@polypyrrole (PMMA@PPy) nanosphere core-shell structure, and then calcines PMMA@PPy and sulfur powder together at high temperature in an inert atmosphere, and PMMA is quickly decomposed by heat to obtain N, S co-doped hollow carbon spheres with Turing surfaces. The prepared N, S co-doped hollow carbon spheres have Turing-shaped raised stripes on the surface, so they have a high specific surface area and abundant crystalline / amorphous interfaces, and are a simple and efficient method for making Turing-structured hollow carbon spheres.
[0004] The present invention provides a N, S co-doped hollow carbon sphere with a Turing surface, wherein the N, S co-doped hollow carbon sphere comprises a shell layer and a hollow inner cavity, and the surface structure of the shell layer of the N, S co-doped hollow carbon sphere is a Turing structure; the particle size of the N, S co-doped hollow carbon sphere is 100-300 nm, the shell layer thickness of the N, S co-doped hollow carbon sphere is 10-20 nm, and the specific surface area is 300-500 m 2 / g.
[0005] Furthermore, in the N, S co-doped hollow carbon sphere, the atomic ratio of doped nitrogen atoms to the total atomic ratio of all elements is 3% to 6%, and the atomic ratio of doped sulfur atoms to the total atomic ratio of all elements on the surface is 4% to 9%.
[0006] The present invention further provides a method for preparing N, S co-doped hollow carbon spheres with a Turing surface, comprising the following steps:
[0007] Step 1: dissolving methyl methacrylate, sodium dodecyl sulfate and an initiator in water, stirring and refluxing the mixed solution under the protection of an inert gas, and performing a polymerization reaction to obtain a polymethyl methacrylate suspension;
[0008] Step 2: adding the polymethyl methacrylate suspension obtained in step 1 into water and stirring at low temperature, dropping pyrrole into the aqueous solution of the polymethyl methacrylate suspension and continuing stirring, adding an initiator to the mixed solution to carry out a polymerization reaction; washing and drying the obtained product to obtain polymethyl methacrylate@polypyrrole;
[0009] Step 3: calcining the polymethyl methacrylate@polypyrrole and sulfur powder obtained in step 2 under the protection of inert gas to obtain N, S co-doped hollow carbon spheres with Turing surface.
[0010] Furthermore, in step 1, the mass volume ratio of methyl methacrylate, sodium dodecyl sulfate, initiator and water is 3mL:1mg:24mg:35mL; and the initiator is potassium persulfate.
[0011] Furthermore, in step 1, the inert gas is argon, the polymerization reaction temperature is 70-80° C., and the polymerization reaction time is 4 hours.
[0012] Furthermore, in step 2, the low-temperature stirring temperature is 0-4° C.; the stirring time after the dropwise addition of pyrrole is 40 min; and the volume ratio of the aqueous solution of the polymethyl methacrylate suspension, pyrrole and initiator is 43.2:1.2:1.
[0013] Furthermore, in step 2, the initiator is ammonium persulfate; the initiator is added in the form of an initiator aqueous solution; the initiator concentration in the initiator aqueous solution is 7.5×10 -3 mol / L; the polymerization reaction temperature is 0-4°C, and the polymerization reaction time is 3h.
[0014] Furthermore, in step 2, the washing is performed with distilled water and ethanol for several times; the drying temperature is 60-80° C., and the drying time is 12 hours.
[0015] Furthermore, in step 3, the mass ratio of the polymethyl methacrylate@polypyrrole to sulfur powder is 1:10-40.
[0016] Furthermore, in step 3, preferably, the mass ratio of the polymethyl methacrylate@polypyrrole to sulfur powder is 1:20.
[0017] Furthermore, in step 3, the inert gas is argon, the calcination temperature is 800° C., the calcination time is 2 h, and the heating rate is 2° C. / min.
[0018] The beneficial effects of the present invention are:
[0019] At present, most of the materials with Turing structure need to be prepared in homogeneous or heterogeneous solutions to form a specific liquid-liquid interface, which has high requirements for experimental operation and environment. The present invention only needs high-temperature calcination in an inert atmosphere to prepare hollow carbon spheres with Turing structure. At the same time, the preparation cost is low, and the output obtained by a single preparation in the laboratory can reach the gram level, which can easily achieve large-scale preparation. The formed N, S co-doped hollow carbon spheres have a high specific surface area and contain rich crystalline / amorphous interfaces. Due to its special structure, it can be applied in a variety of fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 Scanning and transmission electron micrographs of N, S co-doped hollow carbon spheres with Turing surface according to Example 2 of the present invention.
[0021] Figure 2 This is the XRD spectrum of the N, S co-doped hollow carbon sphere with Turing surface according to Example 2 of the present invention.
[0022] Figure 3 This is the XPS spectrum of the N, S co-doped hollow carbon sphere with Turing surface according to Example 2 of the present invention.
[0023] Figure 4 N is the N, S co-doped hollow carbon sphere with Turing surface of Example 2 of the present invention. 2 Adsorption-desorption curve.
[0024] Figure 5 This is a photograph of the yield of N, S co-doped hollow carbon spheres with Turing surface prepared in a single laboratory step according to Example 1 of the present invention.
[0025] Figure 6 This is a diagram of the electromagnetic wave absorption performance of N, S co-doped hollow carbon spheres in Application Example 1. DETAILED DESCRIPTION
[0026] The present invention is further described below in conjunction with the accompanying drawings.
[0027] Unless otherwise specified, the equipment and reagents used in the present invention are conventional commercial products in the art.
[0028] The present invention provides a method for preparing N, S co-doped hollow carbon spheres with a Turing surface, which specifically comprises the following steps:
[0029] (1) A certain amount of methyl methacrylate (MMA), sodium dodecyl sulfate (SDS) and potassium persulfate were dissolved in a certain volume of water, and refluxed at 70 degrees for 4 hours in argon to obtain a suspension of polymethyl methacrylate (PMMA) nanospheres.
[0030] (2) The PMMA suspension was diluted with distilled water and the temperature was lowered to below 4 degrees. A certain amount of pyrrole was added dropwise and stirred evenly. Ammonium persulfate was added as a polymerization initiator to polymerize pyrrole on the surface of PMMA nanospheres to form polymethyl methacrylate@polypyrrole (PMMA@PPy).
[0031] (3) PMMA@PPy and sulfur powder were calcined at 800 °C in argon for 2 h to obtain N, S co-doped hollow carbon spheres with Turing surface.
[0032] In order to further illustrate the present invention, a N, S co-doped hollow carbon sphere with a Turing surface, a preparation method thereof and an application thereof provided by the present invention are described in detail below in combination with embodiments.
[0033] Embodiment 1:
[0034] (1) Dissolve 15 mL of MMA, 5 mg of SDS and 120 mg of potassium persulfate in 175 mL of deionized water. Stir and reflux the mixed solution at 70°C under argon for 4 h. Collect the white suspension in a glass bottle for later use.
[0035] (2) Add 16 mL PMMA to 200 mL H 2 O and stirred in an ice bath below 4°C. Then, 6 ml of pyrrole was added to the above solution and stirred for 40 minutes. Then, 0.34 ml of 2 / g of ammonium persulfate 5mL, stirred in an ice bath for 3 hours. Filter and wash the black precipitate with 500mL of distilled water and 20mL of ethanol. Finally, dry the obtained black precipitate in an oven at 60℃ for 12h.
[0036] (3) 250 mg PMMA@PPy and 2.5 g sulfur powder were placed in the downstream and upstream of the tube furnace respectively and heated to 800 °C in an Ar atmosphere at a heating rate of 2 °C / min for 2 h. The prepared N, S co-doped hollow carbon spheres have a BET specific surface area of about 300 m 2 / g of N,S co-doped hollow carbon spheres with Turing surface. The single laboratory yield can reach about 1.3174g.
[0037] Embodiment 2:
[0038] (1) Dissolve 15 mL of MMA, 5 mg of SDS and 120 mg of potassium persulfate in 175 mL of deionized water. Stir and reflux the mixed solution at 70°C under argon for 4 h. Collect the white suspension in a glass bottle for later use.
[0039] (2) Add 16 mL PMMA to 200 mL H 2 O and stirred in an ice bath below 4°C. Then, 6 mL of pyrrole was added to the above solution and stirred for 40 minutes. Then, 0.34 mL of 2 / g of ammonium persulfate 5mL, stirred in an ice bath for 3 hours. Filter and wash the black precipitate with 500mL of distilled water and 20mL of ethanol. Finally, dry the obtained black precipitate in an oven at 60℃ for 12h.
[0040] (3) 250 mg PMMA@PPy and 5 g sulfur powder were placed in the downstream and upstream of the tube furnace respectively and heated to 800 °C in an Ar atmosphere at a heating rate of 2 °C / min for 2 h. N, S co-doped hollow carbon spheres were prepared. The single laboratory yield can reach about 1.4125 g.
[0041] The morphology characterization results of the N, S co-doped hollow carbon spheres with Turing surface prepared in the embodiment are as follows: Figure 1 As shown. Among them, Figure 1 (a) is the scanning electron microscope (SEM) image of N, S co-doped hollow carbon spheres, with obvious Turing-like raised stripes on the shell surface. Figure 1 (b) is the transmission electron microscope TEM image of N, S co-doped hollow carbon spheres, which shows that N, S co-doped hollow carbon spheres include a shell layer and a hollow cavity. The thickness of the shell layer is about 10 to 20 nm. It can be clearly observed from the high-resolution transmission image that the shell layer has a Turing structure. Figure 2 This is the XRD pattern of the N, S co-doped hollow carbon sphere with Turing surface prepared in this example. The characteristic peak at around 26° corresponds to the (001) crystal plane of graphite carbon, indicating that the main component of the hollow carbon sphere is carbon. Figure 3 The XPS spectrum of the N, S co-doped hollow carbon spheres with Turing surface prepared in this embodiment shows that the N, S co-doped hollow carbon spheres are rich in nitrogen and sulfur elements, and the element contents are: N: 4.77at%, S: 5.71at%. Figure 4 This is the nitrogen adsorption-desorption curve of the N, S co-doped hollow carbon sphere with Turing surface prepared in this example. The specific surface area of the N, S co-doped hollow carbon sphere is 461.06 m 2 / g, indicating that it has a high specific surface area.
[0042] Embodiment 3:
[0043] (1) Dissolve 15 mL of MMA, 5 mg of SDS and 120 mg of potassium persulfate in 175 mL of deionized water. Stir and reflux the mixed solution at 70°C under argon for 4 h. Collect the white suspension in a glass bottle for later use.
[0044] (2) Add 16 mL PMMA to 200 mL H 2 O and stirred in an ice bath below 4°C. Then, 6 mL of pyrrole was added to the above solution and stirred for 40 minutes. Then, 0.34 mL of 2 / g of ammonium persulfate 5mL, stirred in an ice bath for 3 hours. Filter and wash the black precipitate with 500mL of distilled water and 20mL of ethanol. Finally, dry the obtained black precipitate in an oven at 60℃ for 12h.
[0045] (3) 250 mg PMMA@PPy and 10 g sulfur powder were placed in the downstream and upstream of the tube furnace respectively and heated to 800 °C in an Ar atmosphere at a heating rate of 2 °C / min for 2 h. The prepared N, S co-doped hollow carbon spheres had a shell thickness of 15 nm and a BET specific surface area of about 550 m 2 / g of N,S co-doped hollow carbon spheres with Turing surface. The single laboratory yield can reach about 1.5306g.
[0046] Application Example 1:
[0047] 7 mg of N, S co-doped hollow carbon spheres prepared in Example 2 were mixed with 63 mg of paraffin solids, ground evenly, and poured into a mold with an inner diameter of 3 mm and an outer diameter of 7 mm to obtain a ring, which was placed in a vector network analyzer for coaxial testing. Figure 6 The test results show that N, S co-doped hollow carbon spheres have obvious electromagnetic wave absorption performance in the test frequency band, and when the thickness is 2.5mm, the effective absorption bandwidth can reach 4.08GHz. Due to its unique structural advantages, it has excellent electromagnetic wave absorption performance.
[0048] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A N, S co-doped hollow carbon sphere with a Turing surface, characterized in that: The N, S co-doped hollow carbon sphere comprises a shell layer and a hollow inner cavity; the surface structure of the shell layer of the N, S co-doped hollow carbon sphere is a Turing structure; the particle size of the N, S co-doped hollow carbon sphere is 100-300 nm, the shell layer thickness of the N, S co-doped hollow carbon sphere is 10-20 nm, and the specific surface area is 300-500 m 2 / g.
2. A method for preparing N, S co-doped hollow carbon spheres with Turing surface, characterized in that: The following steps are involved: Step 1: dissolving methyl methacrylate, sodium dodecyl sulfate and an initiator in water, stirring and refluxing the mixed solution under the protection of an inert gas, and performing a polymerization reaction to obtain a polymethyl methacrylate suspension; Step 2: adding the polymethyl methacrylate suspension obtained in step 1 into water and stirring at low temperature, dropping pyrrole into the aqueous solution of the polymethyl methacrylate suspension and continuing stirring, adding an initiator to the mixed solution to carry out a polymerization reaction; washing and drying the obtained product to obtain polymethyl methacrylate@polypyrrole; Step 3: calcining the polymethyl methacrylate@polypyrrole and sulfur powder obtained in step 2 under the protection of inert gas to obtain N, S co-doped hollow carbon spheres with Turing surface.
3. The method for preparing a N, S co-doped hollow carbon sphere having a Turing surface according to claim 2, characterized in that: In step 1, the mass volume ratio of methyl methacrylate, sodium dodecyl sulfate, initiator and water is 3 mL: 1 mg: 24 mg: 35 mL; the initiator is potassium persulfate.
4. The method for preparing a N, S co-doped hollow carbon sphere having a Turing surface according to claim 2, characterized in that: In step 1, the inert gas is argon, the polymerization reaction temperature is 70-80° C., and the polymerization reaction time is 4 hours.
5. The method for preparing N, S co-doped hollow carbon spheres with Turing surface according to claim 2, characterized in that: In step 2, the low-temperature stirring temperature is 0-4° C.; the stirring time after the pyrrole is added dropwise is 40 min; and the volume ratio of the aqueous solution of the polymethyl methacrylate suspension, pyrrole and initiator is 43.2:1.2:
1.
6. The method for preparing a N, S co-doped hollow carbon sphere having a Turing surface according to claim 2, characterized in that: In step 2, the initiator is ammonium persulfate; the initiator is added in the form of an initiator aqueous solution; the initiator concentration in the initiator aqueous solution is 7.5×10 -3 mol / L; the polymerization reaction temperature is 0-4°C, and the polymerization reaction time is 3h.
7. The method for preparing N, S co-doped hollow carbon spheres with Turing surface according to claim 2, characterized in that: In step 2, the washing is performed by washing with distilled water and ethanol for several times; the drying temperature is 60-80° C., and the drying time is 12 hours.
8. The method for preparing N, S co-doped hollow carbon spheres with Turing surface according to claim 2, characterized in that: In step 3, the mass ratio of polymethyl methacrylate@polypyrrole to sulfur powder is 1:10-40.
9. The method for preparing N, S co-doped hollow carbon spheres with Turing surface according to claim 8, characterized in that: In step 3, preferably, the mass ratio of the polymethyl methacrylate@polypyrrole to sulfur powder is 1:
20.
10. The method for preparing N, S co-doped hollow carbon spheres with Turing surface according to claim 2, characterized in that: In step 3, the inert gas is argon, the calcination temperature is 800° C., the calcination time is 2 h, and the heating rate is 2° C. / min.
